Challenges of the Nano–Bio Interface in Lateral Flow and Dipstick Immunoassays. Issue 12 (December 2017) - de Puig, Helena; Bosch, Irene; Gehrke, Lee; Hamad-Schifferli, Kimberly
Abstract : Lateral flow assays (LFAs) are highly attractive for point-of-care (POC) diagnostics for infectious disease, food safety, and many other medical uses. The unique optical, electronic, and chemical properties that arise from the nanostructured and material characteristics of nanoparticles provide an opportunity to increase LFA sensitivity and impart novel capabilities. However, interfacing to nanomaterials in complex biological environments is challenging and can result in undesirable side effects such as non-specific adsorption, protein denaturation, and steric hindrance. These issues are even more acute in LFAs where there are many different types of inorganic–biological interfaces, often of a complex nature. Therefore, the unique properties of nanomaterials for LFAs must be exploited in a way that addresses these interface challenges. Trends: LFAs for infectious disease, food safety, and many other applications have been enhanced by nanotechnology. However, interface effects in LFAs are much more complicated, which is problematic because POC devices must be robust, simple, and easy to use. To fully utilize the unique properties of nanotechnology, these interface issues must be understood, controlled, and also leveraged.